2017
DOI: 10.1200/jco.2016.72.0946
|View full text |Cite
|
Sign up to set email alerts
|

Treatment Efficacy, Adherence, and Quality of Life Among Women Younger Than 35 Years in the International Breast Cancer Study Group TEXT and SOFT Adjuvant Endocrine Therapy Trials

Abstract: Purpose To describe benefits and toxicities of adjuvant endocrine therapies in women younger than 35 years with breast cancer (n = 582) enrolled in the Suppression of Ovarian Function Trial (SOFT) and Tamoxifen and Exemestane Trial (TEXT). Methods In SOFT, women still premenopausal after surgery with or without chemotherapy were randomly assigned to tamoxifen alone, tamoxifen plus ovarian function suppression (OFS), or exemestane plus OFS. In TEXT, all received OFS with or without concomitant chemotherapy and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
77
0
7

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(85 citation statements)
references
References 24 publications
1
77
0
7
Order By: Relevance
“…16,21 As this was not observed in patients treated with tamoxifen, this cannot point at an independent prognostic value of age. 22 The incomplete ovarian function suppression by a GnRH agonist was indeed observed in the SOFT-EST trial, 23 where during 12 months of follow-up, 34.2% of the patients had inadequately suppressed (increased) E2 levels, at least once.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…16,21 As this was not observed in patients treated with tamoxifen, this cannot point at an independent prognostic value of age. 22 The incomplete ovarian function suppression by a GnRH agonist was indeed observed in the SOFT-EST trial, 23 where during 12 months of follow-up, 34.2% of the patients had inadequately suppressed (increased) E2 levels, at least once.…”
Section: Discussionmentioning
confidence: 88%
“…On the contrary, supplementary figure S6 of the TEXT/SOFT analyses regarding the combination of exemestane with a GnRH agonist and the additional analyses in women under 35 years of age show, as illustrated by the HRs, a gradually increasing favorable impact on the disease‐free survival with rising age for the combination AI/GnRH agonist in comparison to tamoxifen/GnRH agonist, possibly due to incomplete ovarian function suppression by GnRH agonists in younger patients . As this was not observed in patients treated with tamoxifen, this cannot point at an independent prognostic value of age . The incomplete ovarian function suppression by a GnRH agonist was indeed observed in the SOFT‐EST trial, where during 12 months of follow‐up, 34.2% of the patients had inadequately suppressed (increased) E2 levels, at least once.…”
Section: Discussionmentioning
confidence: 95%
“…These benefits have been confirmed by a recent 8‐year follow‐up study . In women < 35 years of age, the 5‐year breast cancer‐free interval was 67.1% (95% CI, 54.6–76.9%) with tamoxifen alone, 75.9% with tamoxifen plus ovarian suppression (95% CI, 64.0–84.4%), and 83.2% with exemestane plus ovarian suppression (95% CI, 72.7–90.0%) . After 8 years, the rate of freedom from distant recurrence in this age group was 73.8% with tamoxifen alone, 77.5% with tamoxifen plus ovarian suppression, and 82.4% with exemestane plus ovarian suppression .…”
mentioning
confidence: 72%
“…After 8 years, the rate of freedom from distant recurrence in this age group was 73.8% with tamoxifen alone, 77.5% with tamoxifen plus ovarian suppression, and 82.4% with exemestane plus ovarian suppression . These data are expected to increase the number of young, pre‐menopausal women receiving ovarian suppression combined with aromatase inhibitors, which has profound effects on bone health (Box 1).…”
mentioning
confidence: 99%
“…In premenopausal women, tamoxifen has traditionally been first‐line treatment, although a combined analysis of 2 large randomized controlled trials (RCT), Tamoxifen and Exemestane Trial (TEXT) and Suppression of Ovarian Function Trial (SOFT), reported improved 5‐year disease‐free survival with ovarian suppression plus the aromatase inhibitor exemestane compared to ovarian suppression plus tamoxifen (91.1% vs 87.3%, hazard ratio [HR] 0.72; 95% CI 0.60‐0.85; P < .001) . The benefit was significant in premenopausal women with high‐risk ER‐positive, HER2‐negative breast cancer, as defined by clinicopathological characteristics and in patients <35 years of age …”
Section: Introductionmentioning
confidence: 99%